2004
DOI: 10.1038/sj.bjc.6601979
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen treatment reverses the adverse effects of chemotherapy-induced ovarian failure on serum lipids

Abstract: In all, 146 premenopausal women with early stage breast cancer were treated with adjuvant chemotherapy. In addition, 5-year tamoxifen treatment was started after chemotherapy to those 112 patients with hormone-receptor-positive tumours while those with hormone-receptor-negative tumours received no further therapy. The serum lipid levels were followed in both groups. The levels of serum total and low-density lipoprotein (LDL) cholesterol increased significantly after chemotherapy only in patients who developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Monika Sharma et al investigate the longitudinal effect of chemotherapy on lipids in the same group of patients by monitoring the serum lipid profiles of 12 breast cancer patients throughout their multi-agent chemotherapy treatments have obtained the similar results of lipids changes before and after chemotherapy [ 37 ]. Some hypotheses implicate that chemotherapy may directly cause endothelial dysfunction, leading to cytokine alterations, and hence may cause development of lipids [ 38 , 39 ]. Further evidence show that cancer-associated adipocytes modify the cancer cell phenotype leading to a more aggressive behavior [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monika Sharma et al investigate the longitudinal effect of chemotherapy on lipids in the same group of patients by monitoring the serum lipid profiles of 12 breast cancer patients throughout their multi-agent chemotherapy treatments have obtained the similar results of lipids changes before and after chemotherapy [ 37 ]. Some hypotheses implicate that chemotherapy may directly cause endothelial dysfunction, leading to cytokine alterations, and hence may cause development of lipids [ 38 , 39 ]. Further evidence show that cancer-associated adipocytes modify the cancer cell phenotype leading to a more aggressive behavior [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tamoxifen has been well-reported to lower total- and LDL-cholesterol [ 33 36 ] as early as 3 months after treatment initiation [ 34 , 35 ]. Further, the administration of adjuvant tamoxifen after chemotherapy has been observed to reverse dyslipidaemias in premenopausal patients [ 30 ]. In the present study, a significant proportion of patients were found to have dyslipidaemias after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Premenopausal patients with breast cancer also experience detrimental effects from chemotherapy on conditions contributing to MetS; in particular, their body weight may increase, leading to a higher body mass index (BMI) and larger measures of central obesity . Furthermore, chemotherapy in premenopausal patients with breast cancer may induce premature menopause, which is associated with increases in body fat and cholesterol and TRI levels . Therefore, it is important to monitor changes in MetS components in both premenopausal and postmenopausal patients with breast cancer during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Furthermore, chemotherapy in premenopausal patients with breast cancer may induce premature menopause, which is associated with increases in body fat and cholesterol and TRI levels. 1,13 Therefore, it is important to monitor changes in MetS components in both premenopausal and postmenopausal patients with breast cancer during chemotherapy. Understanding the potential detrimental effects of chemotherapy on MetS components and metabolic health is critical to controlling future chronic health problems, improving survival, and enhancing quality of life as clinicians develop survivorship care plans for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%